A TRANSIÇÃO DAS CRIANÇAS DA EDUCAÇÃO INFANTIL PARA O ENSINO FUNDAMENTAL: AS NARRATIVAS DAS PROFESSORAS E AS PRÁTICAS PEDAGÓGICAS PROPOSTAS NO ÚLTIMO ANO DA PRÉ-ESCOLA - FLORIANI, MICHELLE (2024)
The motivating context of this research is that experienced by children of the last year of preschool, before entering elementary school. A time marked by expectations for children, their families and teachers, but also permeated by complex challenges involved in this transition. Often one may want to anticipate preparation practices for later years; for others, the omission or lack of dialogue with children about what is to come does not give due importance to this moment. The concerns about the daily life of teachers and children of the last year of preschool outlined as a central problem the following question: How to structure the pedagogical practices of the last year of the preschool and how do they favor or hinder the transition of children from early childhood education to the first year of elementary school? Among so many crossings, the objective of this construction is based on knowing and problematizing, from the discourses of teachers and the observation of their The transition of children from Early Childhood Education to the first year of Elementary School of two institutions in the city of Guarapuava/ PR. The following specific objectives are intertwined: to understand the conceptions of childhood, child and teaching in Early Childhood Education; to recognize and problematize the experiences of pre-school teachers regarding the pedagogical practice, and understanding about the objectives, purposes and transition of children from Early Childhood Education to Elementary School. The methodological course was outlined from the qualitative approach, supported by cultural studies and the Sociology of Childhood; we use the reading and analysis of national documents, that guide and conducted semi-structured interviews with teachers of the last year of preschool of two educational institutions in the city of Guarapuava/ Paraná. We also chose field observation as a methodological strategy for data generation, in which we seek to direct our gaze to the pedagogical practices carried out by teachers and to apprehend the conceptions of Early Childhood Education that records (field diary) and photographs as a way to preserve the details of the observed situations. The triangulation of data and its analysis made emerge the following categories, thought in an articulated way: a) time/temporality; b) spaces; c) materials/materialities; d) proposals; e) body. The results indicate the lack of knowledge about the meaning of the transition, including what is defined in the documents prepared for early childhood education. Thus, there was no transition thought, organized and dialogued with children, becoming evident the concern to prepare children for the arrival in elementary school.